Analisis Pengendalian Persediaan Bahan Baku Kedelai dengan Metode Economic Order Quantity (EOQ) pada Pabrik Tahu HR Kepuh - Devi Aryani; Sari Marliani; July Yuliawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out how to optimize inventory control for ordering economical raw materials at the HR kepuh tofu factory using the economic order quantity (EOQ) method calculation. This research was conducted using quantitative descriptive methods. Data collection in this research used primary and secondary data obtained by observation and interviews. The results of this research state that the optimal purchase of soybean raw material supplies with EOQ is 788 kg, whereas previously it was 47 kg, so there is a difference of 741 kg. The total cost of raw material inventory before using the EOQ method was IDR 94,665,900 per year while after using the EOQ method it was IDR. 26,267,719 there is a difference of Rp. 68,398,181. The inventory of goods or safety stock that must be provided by the company is 2,278 kg, whereas previously it was only 78 kg, there is a difference of 2,200 kg. The company reordered when the raw materials were at 2,280 Kg, whereas previously it was only 79 Kg, there was a difference of 2,201 Kg.